2009
DOI: 10.3177/jnsv.55.191
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Secretions in the Mesenteric Lymph Node in Stressed Rats

Abstract: Summary To study the effects of different types of stressors on intestinal immune function, the lymphocyte subsets and associated immunoglobulin production in stressed rats were observed. Physical (electric foot shock) or psychological (non foot-shock) stress respectively were induced using a communication box. Rats were exposed to stress for 2 h per day, and the treatment was maintained for 14 consecutive days. Lymphocytes were isolated from the mesenteric lymph node (MLN) and spleen using Lympholyte-Rat. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
11
2
Order By: Relevance
“…This is in good agreement with other reports. [33] GC analysis of the mixtures of linseed oil with α tocopherol (Figure 5b…”
Section: Monitoring Of α Tocopherol Antioxidant Efficacy During Linsementioning
confidence: 99%
“…This is in good agreement with other reports. [33] GC analysis of the mixtures of linseed oil with α tocopherol (Figure 5b…”
Section: Monitoring Of α Tocopherol Antioxidant Efficacy During Linsementioning
confidence: 99%
“…Assays on rats with an electric shock protocol showed that stress suppressed the production of IFN-γ through T cells with TCRαβ in the intraepithelial compartment, while at the same time elevating the level of endogenous glucocorticoids (Zhang et al, 2005). Studies on rodents under psychological stress have also reported a decrease in levels of intestinal SIgA, caused by: (i) an expectation of electric foot shock (Yamamoto et al, 2009), (ii) a continuous back and forth transference from housing cages to metabolic cages (Eriksson et al, 2004), and (iii) immobilization, in some cases combined with exposure to loud noise (Ponferrada et al, 2007; Caso et al, 2009; Zoppi et al, 2012). …”
Section: The Restraint Model and The Influence Of Stress In The Intesmentioning
confidence: 99%
“…Although stress has been regarded as immunosuppressive, it can enhance the levels of IgA (Yamamoto et al, 2009) and CD3+/CD8+ T lymphocytes in the MLN of rats under stress by electric foot shock or exposure to heat (Liu et al, 2012). The capacity of restraint stress to activate the gene expression of purine rich element binding protein A ( pura ) has been reported to be responsible for priming T cells to undergo proliferation (Flint et al, 2005).…”
Section: The Immunomodulatory Mechanisms Of Stress (Table 2)mentioning
confidence: 99%
“…Preparation and analysis of lymphocytes. Lymphocyte culture and analysis were performed as described by Yamamoto et al (27). In brief, mesenteric lymph nodes (MLN) and spleens (SPL) were removed and minced in RPMI 1640 medium (Life Technologies, Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
“…MLN and SPL lymphocyte subpopulations were analyzed by flow cytometry using a FACSCalibur HG (Becton Dickinson) (27). For staining, the lymphocytes were isolated as described above, resuspended at 1.2310 7 cells/ mL, and incubated on ice for 30 min with phycoerythrin-or fluorescein isothiocyanate-conjugated monoclonal antibodies against CD3, CD4, CD8, and CD45RA.…”
Section: Methodsmentioning
confidence: 99%